The Potential Roles of Jamu for COVID-19: A Learn from the Traditional Chinese Medicine - Hartanti, Dwi; Dhiani, Binar Asrining; Charisma, Shintia Lintang; Wahyuningrum, Retno (UI Scholars Hub, 2020)
As the pandemic of the coronavirus disease 2019 (COVID-19) continues while there is no drug and vaccine available, every effort to discover one should be considered. This review aimed to discuss the potential use of jamu, the Indonesian traditional herbal medicine, to deal with COVID-19 by following those of more-established traditional Chinese medicine (TCM). The online literature search using the PubMed database, as well as the circulars from the Indonesian Ministry of Health, were carried out to collect data up to June 07, 2020. The use of TCM for the treatment and prevention of COVID-19 has been officiated in the Chinese National Clinical Guideline on COVID-19 Associated Pneumonia, with shen-fu-tang + su-he-xiang pill and xiang-sha-liu-junzi- tang as the most frequently suggested formulae to treat severe and recovery stages of COVID-19, respectively. In Indonesia, the highly promoted product for the prevention of this disease is likely the adaptation of a TCM formula, while the use of some other formulae, which mainly containing Zingiberaceae, is suggested by the Government for the said purpose. The rationalization of the use of medicinal plants and suggested polyherbal formulae, based on their available pharmacological activity and the bioactive compounds, is also discussed in this review. The use of jamu for COVID-19, however, needs to be carefully considered for the limited scientific data available to support it.